2001
DOI: 10.1046/j.1471-4159.2001.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of citalopram on postsynaptic 5‐hydroxytryptamine1A receptor‐mediated feedback: a microdialysis study in the amygdala

Abstract: Microdialysis was used to assess the involvement of postsynaptic 5-hydroxytryptamine 1A (5-HT 1A ) receptors in the regulation of extracellular 5-HT in the amygdala. Local infusion of the 5-HT 1A receptor agonist¯esinoxan (0.3, 1, 3 mM) for 30 min into the amygdala maximally decreased 5-HT to 50% of basal level. Systemic administration of citalopram (10 mmol/kg) increased 5-HT to 175% of basal level. Local infusion of 1 mM of the 5-HT 1A receptor antagonist WAY 100.635 into the amygdala augmented the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 38 publications
3
55
0
Order By: Relevance
“…Although network changes might represent a central issue in antidepressant treatment (El Mansari et al, 2005), the driving factors are still far from understood. Previous studies in rats demonstrated 5-HT 1A receptor-mediated feedback loops from the medial prefrontal cortex (Casanovas et al, 1999;Sharp et al, 2007) and decreased responsiveness of amygdalar 5-HT 1A heteroreceptors after chronic SSRI treatment (Bosker et al, 2001). Together with desensitization of the raphe nuclei, these studies are consistent with our finding of enhanced 5-HT 1A correlations between amygdala and DRN after sustained escitalopram medication.…”
Section: Association Of 5-ht 1a Bp Nd Between Autoreceptors and Hetersupporting
confidence: 92%
See 1 more Smart Citation
“…Although network changes might represent a central issue in antidepressant treatment (El Mansari et al, 2005), the driving factors are still far from understood. Previous studies in rats demonstrated 5-HT 1A receptor-mediated feedback loops from the medial prefrontal cortex (Casanovas et al, 1999;Sharp et al, 2007) and decreased responsiveness of amygdalar 5-HT 1A heteroreceptors after chronic SSRI treatment (Bosker et al, 2001). Together with desensitization of the raphe nuclei, these studies are consistent with our finding of enhanced 5-HT 1A correlations between amygdala and DRN after sustained escitalopram medication.…”
Section: Association Of 5-ht 1a Bp Nd Between Autoreceptors and Hetersupporting
confidence: 92%
“…In healthy subjects, strong correlations of 5-HT 1A receptors between the dorsal raphe nucleus (DRN) and projection areas were reported (Rabiner et al, 2002;Borg et al, 2006;Drevets et al, 2007). Although these interregional relationships might provide important complementary information on a network level, only few results describe such treatment-induced interactions (Bosker et al, 2001;Sprouse et al, 2001;El Mansari et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is true both in preclinical studies measuring serotonin release with microdialysis [20] and in indirect measures in human volunteers employing, for example, the increase in salivary cortisol as an indirect index of enhanced serotonin activity [21]. In a task of emotional processing, we found that a single dose of the SSRI, citalopram (20 mg), increased the recognition of happy facial expressions [22].…”
Section: (B) Antidepressants and Emotional Processingmentioning
confidence: 82%
“…Postsynaptic 5-HT 1A receptor-mediated feedback has been demonstrated in several terminal field areas of serotonergic innervation, including cortex (Ceci et al 1994;Casanovas et al 1999) and amygdala (Bosker et al 1997). Bosker et al (2001) Electrophysiological studies indicate that chronic treatment with amitriptyline results in the sensitization of postsynaptic neurons to serotonin in the hippocampus, where this response has been shown to be mediated by the 5-HT 1A receptor (de Montigny and Aghajanian 1978;Gallager and Bunney 1978;Chaput et al 1991). In the current study, however, we did not observe an increase in 5-HT 1A receptor-stimulated [ eas examined.…”
Section: Discussionmentioning
confidence: 99%